Women Financial Empowerment through Entrepreneurship in India: A Case Study of Women Entrepreneurs in Food Industry (International Journal of Food and Nutritional Sciences, 2022)
Women are an essential part of the labor market. Their role in the development of the country cannot be ignored. The growing number of women entrepreneurs in India has had a major impact over the economy of the country. Entrepreneurship improves the position of women in society.This paper highlights the growing influence of women in the field of entrepreneurship and how has that proven a positive step towards their financial empowerment.This paper specifically focuses on the women entrepreneurs in India who have made a mark in the field of food and nutrition.